Cenozoic origins of the genus Calliarcys (Insecta, Ephemeroptera) revealed by Micro-CT, with DNA barcode gap analysis of Leptophlebiinae and Habrophlebiinae - Godunko, Roman J; Alba-Tercedor, Javier; Grabowski, Michal; Rewicz, Tomasz; Staniczek, Arnold H (Scientific reports, 2022)
Mayflies (Ephemeroptera) are among the oldest pterygote insects, with the earliest fossils dating back to the Late Carboniferous. Within mayflies, Leptophlebiidae are a highly diverse and widespread group, with approximately 140 genera and 640 species. Whereas taxonomy, systematics, and phylogeny of extant Leptophlebiidae are in the focus of extensive studies, little is known about leptophlebiid fossil taxa. Because fossil remains of Ephemeroptera in sedimentary rocks are relatively rare, inclusions of mayflies in amber are a unique source of information on their evolution and diversity in the past. Leptophlebiidae found in Cenozoic resins mostly belong to the subfamilies Leptophlebiinae (in Eocene Baltic amber) and Atalophlebiinae (in Miocene Dominican and Mexican ambers). In the present contribution, we confirm the first finding of the genus Calliarcys from Eocene Baltic amber by using Micro-CT, which allowed confirming its generic placement by visualizing diagnostic key characters otherwise hidden by a cloud of turbidity. Additionally, we present first molecular data on the extant species Calliarcys humilis Eaton, 1881 from the Iberian Peninsula and the barcode gap analysis for Leptophlebiinae and Habrophlebiinae.
Keywords: Fossils; zvířata; hmyz; Amber; zkameněliny; taxonomické DNA čárové kódování; jantar; Ephemeroptera; rentgenová mikrotomografie; Animals; DNA Barcoding, Taxonomic; X-Ray Microtomography; Insecta